2017
DOI: 10.1093/jme/tjx169
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Plasmodium falciparum (Haemosporida: Plasmodiidae) Infectivity Rates for the Malaria Vector Anopheles arabiensis (Diptera: Culicidae) at Mamfene, KwaZulu-Natal, South Africa

Abstract: Anopheles arabiensis (Patton; Diptera: Culicidae) is a major malaria vector in the southern African region. In South Africa, effective control of this species using indoor-based interventions is reduced owing to its tendency to rest outdoors. As South Africa moves towards malaria elimination there is a need for complementary vector control strategies. One of the methods under consideration is the use of the sterile insect technique (SIT). Key to the successful implementation of an SIT programme is prior knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
3
33
2
Order By: Relevance
“…Currently in KZN, larval source management is employed in an ad hoc uncoordinated manner. The KZN control programme should consider upscaling its use; guided by regularly updated breeding site maps and comprehensive data management, to control out-door resting vector populations associated with sustaining residual transmission in KZN [15,40]. As vector populations with reduced susceptibility to pyrethroids were detected in this study and have been confirmed in neighbouring Mozambique [41], it is imperative that resistance susceptibility testing becomes a routine programmatic activity, with the data generated used to inform insecticide selection.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Currently in KZN, larval source management is employed in an ad hoc uncoordinated manner. The KZN control programme should consider upscaling its use; guided by regularly updated breeding site maps and comprehensive data management, to control out-door resting vector populations associated with sustaining residual transmission in KZN [15,40]. As vector populations with reduced susceptibility to pyrethroids were detected in this study and have been confirmed in neighbouring Mozambique [41], it is imperative that resistance susceptibility testing becomes a routine programmatic activity, with the data generated used to inform insecticide selection.…”
Section: Discussionmentioning
confidence: 90%
“…This study was conducted in areas identified as hotspots of local transmission, namely the municipalities of Jozini (a peri-urban area) and uMhlabuyalingana (rural, border area) in uMkhanyakude district, KZN, over a 6-week period in February and March 2018. Malaria transmission in this region occurs mainly during the hot, wet summer months from September to May, with P. falciparum and Anopheles arabiensis the dominant parasite [14] and vector [15] species, respectively. Annual insecticidebased indoor residual spraying (IRS) of households in communities with reported locally-acquired cases is the core vector control intervention in this area.…”
Section: Study Sitementioning
confidence: 99%
“…This study was conducted in areas identified as hotspots of local transmission, namely the municipalities of Jozini (a peri-urban area) and uMhlabuyalingana (rural, border area) in uMkhanyakude district, KZN, over a six-week period in February and March 2018. Malaria transmission in this region occurs mainly during the hot, wet summer months from September to May, with Plasmodium falciparum and Anopheles arabiensis the dominant parasite [14] and vector [15] species, respectively. Annual insecticide-based indoor residual spraying (IRS) of households in communities with reported locally-acquired cases is the core vector control intervention in this area.…”
Section: Study Sitementioning
confidence: 99%
“…The main malaria vector in South Africa is An. arabiensis [5]. In South Africa, malaria primarily occurs in the Limpopo, Mpumalanga and KwaZulu-Natal provinces.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it practically impossible to eliminate An. arabiensis using current control methods, contributing to the ongoing transmission of residual malaria in South Africa [5].…”
Section: Introductionmentioning
confidence: 99%